The Diagnostic Accuracy of Shoulder Ultrasound For Rotator Cuff Pathology Compared to Magnetic Resonance Imaging as a Gold Standard - Aziz, Sadaf; Nigar, Falak; Baloch, Sadaf Khan; Atif Latif; Shafiq, Mariam; Mallhi, Ejaz Ashraf (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the diagnostic accuracy of ultrasound in the local population for rotator cuff injury keeping magnetic resonance imaging (MRI) as a gold standard. Study Design: Diagnostic accuracy cross-sectional study. Place and Duration of Study: Department of Radiology, Combined Military Hospital, Multan Institute of Medical Sciences- CIMS) Multan, Pakistan, from Apr to Oct 2022. Methodology: A total of 169 patients with clinically suspected rotator cuff injury were selected by consecutive sampling. Subjects aged 25 to 65 years of either gender presenting with clinically suspected rotator cuff tear were selected for the study. Patients with prosthetic implants, pacemakers and fractures of clavicle, scapula, proximal humerus or having contraindications for MRI were excluded from the study. Ultrasound and MRI were done on each patient by separate operators. Data on diagnoses was collected and analyzed on SPSS v 23. Results: A total sample of 169 patients with clinically suspected rotator cuff injury were enrolled. The mean age was 37.39± 8.97 years (range 25-65) of which 127(74.15%), were between 25 to 45 years of age. There was a preponderance of males: 120(71%). The diagnostic parameters for ultrasound were sensitivity-92.86%, specificity-90.59%, PPV-90.70%, NPV-92.77% and diagnostic accuracy-91.72%. Conclusion: The diagnostic accuracy of ultrasound is comparable to that of MRI for detecting rotator cuff tears, suggesting a significant role for ultrasound in assessing rotator cuff tears.